2010
DOI: 10.1091/mbc.e10-03-0176
|View full text |Cite
|
Sign up to set email alerts
|

Scyl1 Facilitates Nuclear tRNA Export in Mammalian Cells by Acting at the Nuclear Pore Complex

Abstract: We provide evidence that Scyl1 is also a cytoplasmic component of the nuclear aminoacylation-dependent tRNA export pathway. Scyl1, like the Saccharomyces cerevisiae Cex1p, may collect aminoacyl-tRNAs from the nuclear tRNA export receptors at the cytoplasmic side of the NPC and channel them to eEF-1A for use in protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 70 publications
(164 reference statements)
3
31
0
Order By: Relevance
“…29 Moreover, we previously demonstrated that the Arabidopsis lysine amber suppressor tRNA mutant (tRNA Lys am ) with the C11:G24 base pair changed to G11:C24 accumulated entirely in the nucleus of transiently-transformed BY-2 cells, 30 similar to the nuclear retention observed for analogous G11:G24 mutants of tRNA Tyr am in S. cerevisiae 31,32 and tRNA Ser am in mammalian-cultured (COS7) cells. 33 Finally, in view of the finding that nutrient stress does not affect nuclear-cytoplasmic tRNA trafficking in plants, we confirmed that nuclear accumulation of tRNA can be detected in plant cells when the nuclear tRNA export process is affected by disrupting nuclear tRNA aminoacylation. As mentioned above, newly-matured tRNAs undergo aminoacylation quality assurance in the nucleolus to verify that they are functional before being exported to the cytoplasm and that this serves as a critical first step in the nuclear tRNA export process, since inhibition of aminoacyltRNA synthetase activities in mammalian cells and S. cerevisiae blocks nuclear export of their cognate tRNAs.…”
supporting
confidence: 75%
“…29 Moreover, we previously demonstrated that the Arabidopsis lysine amber suppressor tRNA mutant (tRNA Lys am ) with the C11:G24 base pair changed to G11:C24 accumulated entirely in the nucleus of transiently-transformed BY-2 cells, 30 similar to the nuclear retention observed for analogous G11:G24 mutants of tRNA Tyr am in S. cerevisiae 31,32 and tRNA Ser am in mammalian-cultured (COS7) cells. 33 Finally, in view of the finding that nutrient stress does not affect nuclear-cytoplasmic tRNA trafficking in plants, we confirmed that nuclear accumulation of tRNA can be detected in plant cells when the nuclear tRNA export process is affected by disrupting nuclear tRNA aminoacylation. As mentioned above, newly-matured tRNAs undergo aminoacylation quality assurance in the nucleolus to verify that they are functional before being exported to the cytoplasm and that this serves as a critical first step in the nuclear tRNA export process, since inhibition of aminoacyltRNA synthetase activities in mammalian cells and S. cerevisiae blocks nuclear export of their cognate tRNAs.…”
supporting
confidence: 75%
“…NTKL has been found to exhibit multiple subcellular localizations, including golgi apparatus, cytoplasm, centrosomes and nucleus [13]. Golgi NTKL has been reported to regulate golgi morphology and interact with Cop1 vesicles [14], while centrosome NTKL was reported to play a role in cell division [15]. In the present study, we found that NTKL, which was regulated by CHD1L, was frequently overexpressed in primary HCC cases.…”
Section: Introductionsupporting
confidence: 57%
“…Scyl1 collects aminoacyl-tRNAs from Los1p on the cytoplasmic side of the NPC and channels them to elongation factor which further delivers it to the ribosome. 12 In summary, the nuclear channeling is required for tRNA maturation and aminoacylation, shipping aminoacyl-tRNA from the nucleus to the cytosol and its final delivery to the ribosome. In the cytosol, channeling mediates the transfer of de-acylated tRNA from the ribosome directly to the aminoacyl-tRNAsynthetases (ARS), then the association of aminoacylated tRNAs with elongation factor and subsequent transfer of aminoacyltRNAs to the ribosomes.…”
Section: Do Not Distributementioning
confidence: 99%